Криміналістична характеристика умисних вбивств із мотивів расової, національної чи релігійної нетерпимості - Галагуря, Є. Л.; Halahuria, Ye. L. (Право і Безпека. - 2016. - № 2 (61). - С. 65–69, 2016)
Розглянуто поняття та сутність криміналістичної характеристики умисних вбивств із мотивів расової, національної чи релігійної нетерпимості. Досліджено складові елементи криміналістичної характеристики вчинення таких убивств. Запропоновано авторське визначення поняття криміналістичної характеристики умисних вбивств із мотивів расової, національної чи релігійної нетерпимості.

Forensics – is an applied legal science that studies the laws of preparation, commission and solving a crime, the origin and existence of its traces, collection, research, evaluation and use of evidence, as well as develops a system of special techniques, methods and means based on the cognition of these laws and used during the preliminary investigation for the prevention, detection and investigation of crimes and during criminal proceedings in a court. Forensic characteristics are considered as a separate scientific theory and system of scientific provisions and practical recommendations on constructing the system of forensic significant features of certain sets of crimes, and it is important for the identification, detection and investigation of criminal offenses. One of the elements of forensic characteristics is to study individual psychological characteristics of a person who has committed a crime, which is an obligatory prerequisite to ensure rapid, complete and impartial investigation of crimes, including murders of racial, national or religious intolerance. Besides, establishment of forensic characteristics of a person who has committed a criminal offense is essential to prevent this category of crimes and their successful solving. According to the investigative practice, criminal proceedings started by the fact of commission of a murder with the motives of racial, national or religious intolerance have fairly complex evidence base, and for effective investigation activities on solving this category of proceedings an investigator should consider forensic characteristics. The author has concluded that under forensic characteristics of murders with the motives of racial, national or religious intolerance we should understand information about the circumstances, the personality of a perpetrator, method, mechanism, place and time of the commission of this type of a crime and to ensure their effective use in solving the strategic and tactical tasks of pre-trial investigation.

Рассмотрены понятие и сущность криминалистической характеристики умышленных убийств по мотивам расовой, национальной или религиозной нетерпимости. Исследованы составляющие элементы криминалистической характеристики совершения таких убийств. Предложено авторское определение понятия криминалистической характеристики умышленных убийств по мотивам расовой, национальной или религиозной нетерпимости.
Forensic characteristics of murders by the motives of racial, national or religious intolerance
Криминалистическая характеристика умышленных убийств по мотивам расовой, национальной или религиозной нетерпимости
Галагуря, Є. Л. Криміналістична характеристика умисних вбивств із мотивів расової, національної чи релігійної нетерпимості / Є. Л. Галагуря // Право і Безпека. - 2016. - № 2. - С. 65-69.
Галагуря Є. Л. "Криміналістична характеристика умисних вбивств із мотивів расової, національної чи релігійної нетерпимості." Право і Безпека 2 (2016): 65-69.
Halahuria, Y.L. (2016), “Forensic characteristics of murders by the motives of racial, national or religious intolerance” [“Kryminalistychna kharakterystyka umysnykh vbyvstv iz motyviv rasovoi, natsionalnoi chy relihiinoi neterpymosti”], Pravo i Bezpeka, No. 2, pp. 65–69.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; криміналістична характеристика; кримінальне правопорушення; умисне вбивство; мотив расової, національної чи релігійної нетерпимості; жертва злочину; forensic characteristics; criminal offense; murder; motive for racial, national or religious intolerance; victim of a crime; криминалистическая характеристика; уголовное правонарушение; умышленное убийство; мотив расовой, национальной или религиозной нетерпимости; жертва преступления